2022
DOI: 10.1371/journal.pone.0274481
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting local plant knowledge in isolated communities from Patagonian steppe: Metacommunity theory is revealed as a methodological approach

Abstract: The Patagonian steppe is a refuge for several indigenous peoples who live in relatively isolated communities, depending heavily on natural resources for their activities, health, and food security. The local ecological knowledge is a reservoir that generates full wellbeing and for which it must be the object of protection and local development. In this study, we aimed to find which factors can influence local ecological knowledge from a metacommunity on the Patagonian steppe. We analyzed variation in knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
4
0
2
Order By: Relevance
“…For example, in Gastre there is a much greater redundancy of plants with analgesic effects, and in Lagunita there is a much greater redundancy of plants used to treat respiratory and circulatory conditions compared to the other two communities. Considering the short distance between the communities and the close bond between them, which make it characterized as a metapopulation (see Santoro et al, 2022), the difference found between the medicinal categories should not be related to epidemiological differences. A hypothesis that we can raise to be investigated in the future is that this difference could reflect possible other treatment strategies that may be preferred over plants specifically for these treatments in some communities, such as the use of biomedicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Gastre there is a much greater redundancy of plants with analgesic effects, and in Lagunita there is a much greater redundancy of plants used to treat respiratory and circulatory conditions compared to the other two communities. Considering the short distance between the communities and the close bond between them, which make it characterized as a metapopulation (see Santoro et al, 2022), the difference found between the medicinal categories should not be related to epidemiological differences. A hypothesis that we can raise to be investigated in the future is that this difference could reflect possible other treatment strategies that may be preferred over plants specifically for these treatments in some communities, such as the use of biomedicine.…”
Section: Discussionmentioning
confidence: 99%
“…When analysing edible plants in Patagonia Argentina, Chamorro & Ladio (2020) conclude that native and exotic species superpose at different levels and that the living heritage of Patagonian edible and medicinal plants appears to have undergone hybridization processes, such that exotic cosmopolitan species play an increasingly significant role. This increasingly important role of exotic species is intrinsically linked to the importance of home gardens since a previous study in the same communities showed that 100% of the species cultivated in these communities are exotic and that cultivation is done mostly in home gardens (Santoro et al, 2022). Similar results in terms of the prevalence of medicinal and edible exotic plants in home gardens were found in other rural and urban communities of the region (Eyssartier et al, 2009; Longo Blasón et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Por ejemplo, en Gastre hay una redundancia mucho mayor de plantas con efectos analgésicos, y en Lagunita hay una redundancia mucho mayor de plantas utilizadas para tratar afecciones respiratorias y circulatorias en comparación con las otras dos comunidades. Considerando la corta distancia entre las comunidades y el estrecho vínculo entre ellas, que hacen que se caracterice como una metapoblación (ver Santoro et al, 2022), la diferencia encontrada entre las categorías medicinales no debería estar relacionada con diferencias epidemiológicas. Una hipótesis que podemos plantear para ser investigada en el futuro es que esta diferencia podría reflejar posibles otras estrategias de tratamiento que pueden ser preferidas sobre las plantas específicas para estos tratamientos en algunas comunidades, como el uso de biomedicina.…”
Section: Discussionunclassified
“…Al analizar las plantas comestibles en la Patagonia Argentina, Chamorro and Ladio (2020) concluyen que las especies nativas y exóticas se superponen en diferentes niveles y que el patrimonio vivo de plantas comestibles y medicinales patagónicas parece haber sufrido procesos de hibridación, de manera que las especies exóticas cosmopolitas juegan un papel cada vez más significativo. Este papel cada vez más importante de las especies exóticas está intrínsecamente ligado a la importancia de los huertos familiares, ya que un estudio previo en las mismas comunidades mostró que el 100% de las especies cultivadas en estas comunidades son exóticas y que el cultivo se realiza mayoritariamente en huertos familiares (Santoro et al, 2022). Resultados similares en cuanto a la prevalencia de plantas exóticas medicinales y comestibles en los huertos familiares fueron encontrados en otras comunidades rurales y urbanas de la región (Eyssartier et al, 2009; Longo Blasón et al, 2022).…”
Section: Discussionunclassified
“…The knowledge on medicinal plants and fungi mixed in magical rituals and customs is mostly preserved in those areas with logistically or financially difficult access to a doctor or veterinarian (Howes et al, 2020). A considerable body of literature covers interesting studies from high mountains (e.g., Tucakov, 1997;Pullaiah et al, 2017;Petelka et al, 2020), from steppe and grassland landscapes (e.g., Molares and Ladio, 2009;Pozdnyakova et al, 2022;Santoro et al, 2022) to from more or less pristine forests (e.g., Uprety et al, 2012;Rodrigues et al, 2021;Kolosova et al, 2022). Old herbal scripts in monasteries showed that herbalists have been always part of the medicinal landscape, even in easily accessible regions before the advent of conventional medicine (Green, 1989;Sabatini, 1994), but were pushed back there more quickly, despite many conventional drugs being developed based on natural remedies (Clément, 2005;Pan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%